Complement in Human Pre-implantation Embryos: Attack and Defense - Reichhardt, Martin P.; Lundin, Karolina; Lokki, A. Inkeri; Recher, Gaëlle; Vuoristo, Sanna; Katayama, Shintaro; Tapanainen, Juha S.; Kere, Juha; Meri, Seppo; Tuuri, Timo (Frontiers in Immunology, 2019)
It is essential for early human life that immunological responses to developing embryos are tightly regulated. An imbalance in the activation and regulation of the human complement system occurs in pregnancy complications, such as pre-eclampsia and recurrent miscarriage. We hereby present the first full analysis of the expression and deposition of complement molecules in human pre-implantation embryos. Thus far, immunological imbalance has been considered in stages of pregnancy following implantation. We here show that complement activation and deposition takes place on developing human embryos already at the pre-implantation stage. Using confocal microscopy, we observed deposition of activation products such as C1q, C3 and C5 on healthy developing embryos, which highlights the need for strict complement regulation. The early embryos express the complement membrane inhibitors CD46, CD55 and CD59 and bind the soluble regulators C4bp and factor H. These findings show that complement targets human embryos, and indicate potential adverse pregnancy outcomes, if regulation of activation fails. In addition, single-cell RNA sequencing of embryos at oocyte, zygote, 4-cell and 8-cell stages showed expression of complement genes, e.g. C1s, C2, C3, C5, factor B and factor D. This shows that the embryonic cells themselves have the capacity to express C3 and C5, which may become activated and function as mediators of cellular signaling. The specific local embryonic expression of complement components, regulators, and deposition of activation products on the surface of embryos suggests that complement has immunoregulatory functions and may impact cellular homeostasis and differentiation at the earliest stage of human life.